Fiscal policy in the European Monetary Union: how can fiscal discipline be achieved? - Díaz-Roldán, Carmen; Montero-Soler, Alberto (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
From the beginning, the success of the European Economic and Monetary Union (EMU) seems to rely on the benefits of the single currency, the higher degree of integration of financial markets, and also on the sound public finances guaranteed by the set of fiscal rules provided by the EMU. When signing the Stability and Growth Pact, Member States committed themselves to reach a medium-term budgetary position close to balance. The aim of this paper is to investigate how fiscal discipline would be achieved. In particular, we will analyse the interaction among those EMU members showing a relatively high level of public debt and those that follow a strict fiscal discipline; paying special attention to the case of the new Member States
Argumenta Oeconomica, 2011, Nr 2 (27), s. 5-14
Keywords: fiscal discipline; stabilization; monetary unions; Unia Gospodarcza i Walutowa; waluta wspólnego rynku; polityka fiskalna